DESIGN OF THE MAPPING OF ORANG UTAN WITH SPATIAL DATA APPROACH TO WEB-BASED GEOGRAPHIC INFORMATION SYSTEMS - Jadiaman Parhusip; Rony Teguh; Liyando Hermawan Hasibuan (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2018)
Orangutans are the only great apes that live in Asia and have the most threatenedstatus in the world. Currently there are three types of orangutans in Indonesia; the Sumatranorangutan (Pongo abelii), the Borneo orangutan (Pongo pygmaeus) and the Tapanuliorangutan (Pongo tapanuliensi). The types of colors that enter critical status are endangered(critical) based on International Unity for Nature Conservation in 2017. Approximately 75%of the distribution of orangutans will be outside the sexuality area need data distributionand orangutan population to meet data needs for the benefit of orangutans.This study used a method to collect data which were of library studies, data retrieval,consultation and discussion studies. After the data was collected, it was conducted needanalysis and system design using the W2000 Software Development Method, which includedprocess design, database design, menu structure design and interface design. Then thesystem implementation utilized Google Map Service and the PHP programming languagebased on the website with the MySQL database.The results of the testing are several locations of orangutan nests where every pointowns information in the form of the number of orangutans and their population. The resultsof this study are the mapping of orangutan’s nests with a GIS web-based spatial dataapproach that will provide information on nest position, nest density, orangutan populationdensity which is at the position of the nest radius.